Sea surface temperature change in the Black Sea under climate change: A simulation of the sea surface temperature up to 2100 - Sakalli, Abdulla; Basusta, Nuri (Wiley, 2018)
Surface temperature of the Black Sea increased due to climate change during the 20th century and continues to rise. Here we present by in situ data-corrected remote-sensed SST data covering a 34-year period (1982-2015). Using a linear black box model, we predicted the Black Sea surface temperature (SST) up to 2100. During the 34-year study period, we detected a 0.64 degrees C increase in SST per decade. The largest monthly fluctuations in SST were during late summer (August) and autumn (November). The rate of SST increase has almost caught up with the worst climate change scenario for the future. At the end of this century, the relative increase in average Black Sea SST is predicted to be 5.1 degrees C. In summary, our data show sea surface warming during recent decades, and we predict that this warming is likely to continue under the present environmental condition. The warming of the sea seems to also influence the amount of caught anchovies in the Black Sea. After 1993, the amount of captured anchovies in the southern Black Sea was drastically decreased with increased SST.
Keywords: anchovy; Black Sea warming; CMEMS; remote sensing; SST